2010
DOI: 10.4321/s0213-61632010000200002
|View full text |Cite
|
Sign up to set email alerts
|

Insight, psychosis and aggressive behaviour in mania

Abstract: -Background and Objectives: Aggressiveness is a common component of manic symptoms. The aim of this study was to determine the clinical characteristics associated with aggressive behaviour in bipolar patients with acute manic episodes.Methods: A study was carried out with 173 patients who met the DSM-IV criteria for manic or mixed bipolar disorder. Clinical and demographic variables were evaluated using the Positive and Negative Symptoms Scale (PANSS), the Young Mania Rating Scale (YMRS), the Brief Psychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
7
0
2
Order By: Relevance
“…Similarly to our findings, around half of the patients attending the psychiatric ER were psychotic patients and presented a moderate to severe disease according to PANSS-EC. Other studies have assessed only bipolar disorder [19] with similar results. Romania and Portugal were also highly represented with 115 and 65 episodes of agitation recorded in 3 centers each and, as far as we know, our study provides the first epidemiological data for acute agitation in these two countries.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly to our findings, around half of the patients attending the psychiatric ER were psychotic patients and presented a moderate to severe disease according to PANSS-EC. Other studies have assessed only bipolar disorder [19] with similar results. Romania and Portugal were also highly represented with 115 and 65 episodes of agitation recorded in 3 centers each and, as far as we know, our study provides the first epidemiological data for acute agitation in these two countries.…”
Section: Discussionsupporting
confidence: 58%
“…Aggressive or violent behavior in bipolar patients usually appears during acute manic episodes[ 137 - 139 ] and is a common cause of hospitalization in this population[ 130 , 140 - 142 ]. Involuntary hospitalization for acute mania is significantly associated with higher rates of aggression/violence and lower rates of insight[ 109 , 143 ].…”
Section: Aggression In Different Psychiatric Disordersmentioning
confidence: 99%
“…Involuntary hospitalization for acute mania is significantly associated with higher rates of aggression/violence and lower rates of insight[ 109 , 143 ]. A clear association was found between the presence and severity of aggression during a manic episode and psychotic symptoms[ 130 , 144 ]. Patients with mood-incongruent psychotic symptoms are more prone to agitation or aggression[ 145 - 149 ].…”
Section: Aggression In Different Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…28 few studies showed correlation between lower level of insight and higher severity of affective episode or presence of psychotic symptoms. 13,14 Other studies state that lower insight was associated with more hostility and lower impulse control, 39 more aggressive behavior, 40 and worse clinical course. 41 Yet other studies found correlation between lower insight and higher impairment of cognition, especially memory, emotional learning, general intelligence and psychomotor function, comprehension and perceptual-motor skills, attention, verbal fluency and executive function, and information processing speed.…”
Section: Sample Characteristics and Associations Between Demographic mentioning
confidence: 99%